PENGARUH CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PADA GEPREK BENSU CABANG PEKANBARU - Intan Larasati; Arief Riva’i (VALUTA, 2022)
This study, uses two variables, namely the celebrity endorser as the independent variable (X) and the purchase decision as to the dependent variable (Y). This research was conducted with the aim of knowing the effect of celebrity endorsers on purchasing decisions at the Pekanbaru branch of Geprek Bensu. The data used in this study are primary data collected through a questionnaire. The hypothesis of this study is that there is an influence of celebrity endorsers on purchasing decisions at the Geprek Bensu Pekanbaru branch. To determine the effect of these variables, indicators of the celebrity endorser variable are used, namely attractiveness, trust, and expertise, as well as indicators of purchase decisions, namely problem recognition, information search, alternative evaluation, purchase decisions, and post-purchase behavior. Then the data processing technique used simple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing (T-test) using SPSS 25. Based on the analysis using the simple linear regression statistical method Y = 21.902 + 0.546X which shows the effect of celebrity endorser (X) the purchase decision (Y) is positive. Furthermore, the results of the correlation coefficient test show the correlation value of the two variables, namely celebrity endorser and purchasing decisions of 0.865 with a positive direction and the level of the relationship is very strong and significant. Furthermore, the results of hypothesis testing, the T-test is 16.717 with sig 0,000 Obtained t table is 1.9855 in other words T count is greater than the T table (16.717> 1.9855). So it can be concluded that Ho is rejected and Ha is accepted, or it can be interpreted that celebrity endorsers have an effect on purchasing decisions or there is a positive and significant influence between celebrity endorsers on purchasing decisions at the Geprek Bensu Pekanbaru branch. The amount of the coefficient of determination is 0.748 (74.8%), which means that celebrity endorsers have an influence of 74.8% on purchasing decisions and 25.2% are influenced by other factors.